SURKHAN OASIS PILGRIMAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article is devoted to the analysis of the construction of ancient historical monuments, architectural styles, location of historical monuments, history and their study in the Surkhandarya region, which has a worthy place in the Islamic civilization.